Thyroid gland: physiology and pathology (a short review) - AL- Mahdawi, Fatimah; Mohammed, Mazin; Taher, Mustafa; Al-Mahdawi ,A. S. Muthanna; Nameer Fadhil alkalifa; Kadi, Ammar; Potoroko, Irina; Chemek, Marouane (ASJ - Academic Science Journal, 2024)
One of the main parts of the endocrine system is the thyroid gland, it produces thyroid hormones, tetraiodothyronine, and triiodothyronine, which are important for metabolic health. In this article, we review the most important thyroid hormones and the imbalance in these hormones. The thyroid hormones control various metabolic processes, involving expenditure of energy and growth, common thyroid disfunction include excessive activity and un excessive activity of the thyroid gland.